2014
DOI: 10.1159/000357483
|View full text |Cite
|
Sign up to set email alerts
|

Lepidopteran Sex Determination: A Cascade of Surprises

Abstract: Sex determination is a developmental pathway that fixes the sexual fate (male or female) of an individual at early stages of embryonic development. This pathway is ideally suited for evolutionary studies given the astoundingly diverse mechanisms found in the animal kingdom. In particular, insects use multiple different cues to specify the sexual fate of an individual. In this review, we focus on genes and genetic interactions involved in the sex determination of insect species belonging to the order Lepidopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 76 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…In insects, dsx is a downstream transcription factor in the sex determination pathway; peak expression of sex‐specific isoforms during embryogenesis may coincide with the time of sex determination events during embryogenesis . Although male‐specific splicing of dsx represents the default mode in dipteran and other insects, female‐specific splicing of dsx is the default in lepidopteran insects . In B. mori , an increase in levels of the male‐specific dsx revealed that sex determination occurs between 21 and 24 h post oviposition (hpo), facilitating discovery of the primary determiner of sex, a female‐specific piRNA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, dsx is a downstream transcription factor in the sex determination pathway; peak expression of sex‐specific isoforms during embryogenesis may coincide with the time of sex determination events during embryogenesis . Although male‐specific splicing of dsx represents the default mode in dipteran and other insects, female‐specific splicing of dsx is the default in lepidopteran insects . In B. mori , an increase in levels of the male‐specific dsx revealed that sex determination occurs between 21 and 24 h post oviposition (hpo), facilitating discovery of the primary determiner of sex, a female‐specific piRNA .…”
Section: Resultsmentioning
confidence: 99%
“…53 Although male-specific splicing of dsx represents the default mode in dipteran and other insects, female-specific splicing of dsx is the default in lepidopteran insects. 54 In B. mori, an increase in levels of the male-specific dsx revealed that sex determination occurs between 21 and 24 h post oviposition (hpo), facilitating discovery of the primary determiner of sex, a female-specific piRNA. 55 To determinate the key stage for sex determination in A. ipsilon, we used RT-PCR to investigate the expression patterns of Aidsx during embryonic development.…”
Section: Key Stage Of Sex-determination In a Ipsilon Embryosmentioning
confidence: 99%
“…In the silkworm B. mori , the male is the homogametic sex and the female is the heterogametic sex. Bmdsx is the downstream gene of the sex determination cascade (Nagaraju et al ., ). The gene products of Bmdsx play essential roles in silkworm sexual development.…”
Section: Discussionmentioning
confidence: 97%
“…S1. Thirty candidate genes within the sex determination pathway were selected from the genes categorized as ‘sex determination (BSID: 492283)’ in the NCBI BioSystems database (http://www.ncbi.nlm.nih.gov/biosystems/) (Geer et al ., ) as well as genes previously reported in D. melanogaster and B. mori (Schütt and Nöthiger, ; Nagaraju et al ., ). The available candidate proteins from D. melanogaster , A. mellifera and B. mori were used as references to screen the B. tabaci Q genome (Xie et al ., ) using the tblastn algorithm with an e ‐value threshold of 10 −5 .…”
Section: Methodsmentioning
confidence: 97%